Tahfiz AI-Muqarrabin school website /Aisyah Fathiah Othman - Othman, Aisyah Fathiah (2012)
Tahfiz Al-Muqarrabin is a private school that teaches their students basic subject and also teaches the students in conquering Al-Quran and memorizing Al-Quran. It is a boarding school. Tahfiz Al-Muqarrabin is a new school and consist of a small community but involve parents from the country all over Malaysia. This situation has caused problems to the school and also to the community. Therefore, the decision to create this website is made. Waterfall model is used in order to help is creating this website. Waterfall model has five phases consist of requirement, design, implementation, verification and documentation. The website will allow teachers to register new students, register new subjects, register new activity, update data and also delete data. The website will also display the information about the school. As a conclusion, the website will help the school in reducing the problem faced by the school.